Snow density profiles at Kottaspegel traverse in 2024-2025 - Heitmann, Filip; Zeising, Ole; Eisen, Olaf (In: Eisen, Olaf (2024): Snow density profiles from Neumayer station [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.963323, 2025)
This is a collection of shallow snow density data sets from overland traverse between Neumayer Station III and Kottas camp in January/February 2025. Sampling during the Kottas traverse was carried out by O. Zeising and F. Heitmann. Sampling device was a 1 m long and 9,05 cm diameter Kovacs ice corer Mark II (Registry Item No 13278, https://registry.o2a-data.de/items/13278). Density was determined as bulk density by dividing the net weight of the snow core by the volume of the snow core (determined from length of the snow core and diameter of the coring device).
Keywords: Dronning Maud Land; Neumayer Station; snow accumulation; snow cores; snow density; snow pit